2016
DOI: 10.1007/s00167-016-4305-9
|View full text |Cite
|
Sign up to set email alerts
|

Current state of computer navigation and robotics in unicompartmental and total knee arthroplasty: a systematic review with meta-analysis

Abstract: Recently, there is a growing interest in surgical variables that are intraoperatively controlled by orthopaedic surgeons, including lower leg alignment, component positioning and soft tissues balancing. Since more tight control over these factors is associated with improved outcomes of unicompartmental knee arthroplasty and total knee arthroplasty (TKA), several computer navigation and robotic-assisted systems have been developed. Although mechanical axis accuracy and component positioning have been shown to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
110
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(114 citation statements)
references
References 139 publications
0
110
1
Order By: Relevance
“…It has been demonstrated that RATKA is able to accurately and consistently achieve the desired implant placement and alignment. [13][14][15] However, there is a paucity of prospective studies demonstrating that the functional outcomes achieved using robotic technology are superior to manual techniques in terms of patient satisfaction and functional abilities. Therefore, the purpose of this study was to assess short-term patient satisfaction and functional outcomes in robotic-assisted versus manual TKA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that RATKA is able to accurately and consistently achieve the desired implant placement and alignment. [13][14][15] However, there is a paucity of prospective studies demonstrating that the functional outcomes achieved using robotic technology are superior to manual techniques in terms of patient satisfaction and functional abilities. Therefore, the purpose of this study was to assess short-term patient satisfaction and functional outcomes in robotic-assisted versus manual TKA patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that robotic-arm-assisted TKA (RATKA) is able to accurately and consistently achieve the desired implant placement and alignment. [13][14][15] Although bone cuts and implant placement accuracy and precision are important for long-term implant survivorship, [16][17][18][19] there is a paucity of prospective studies comparing the outcomes achieved using robotic technology versus manual techniques in terms of patient satisfaction and functional abilities. One recent retrospective study has demonstrated significantly lower pain scores and higher satisfaction indices in patients who underwent RATKA, when compared with manual TKA.…”
mentioning
confidence: 99%
“…In a meta-analysis of seven studies and three registries, van der List et al 28 reported the difference in the annual revision rate (ARR) of computer navigation versus conventional TKA surgery in 4 70 231 patients. Analysis showed an ARR of 0.55 in patients who underwent computer-navigated TKA surgery and an ARR of 0.56 in patients who underwent conventional TKA surgery (P=0.58).…”
Section: Types Of Casmentioning
confidence: 99%
“…The Stryker/MAKO haptic guided robot (MAKO Surgical Corp) has the largest market share with 20% for UKA. Since the introduction in 2005, over 50 000 have been performed with nearly 300 robotic systems nationally 33 80 84…”
Section: Current State Of the Artmentioning
confidence: 99%
“…These advances will be implemented by means of simplifying the process and minimises the learning curve. Critical domains will possibly include preoperative analysis, intraoperative sensors and robotically controlled instrumentation 84. Currently, some sort of imaging modality is necessary in order to perform preoperative planning, depending on the type of robotic system.…”
Section: Current State Of the Artmentioning
confidence: 99%